Dynamic Imaging of the Sodium Phosphate Cotransporters - Blaine, Judith (2011)
Although in vivo and cell culture studies have provided useful information about the regulation of the sodium phosphate (NaPi) cotransporters, such studies are unable to provide information at the molecular level about interactions between proteins. The NaPi proteins are found within both intestinal and renal brush border microvilli, and previous work has shown that these microvilli contain scaffolding proteins (PDZ proteins) and myosin motors. The recent development of several advanced imaging techniques has allowed detailed analysis of how NaPi proteins interact with scaffolding proteins and myosin motors. Using techniques such as apical total internal reflection fluorescence microscopy, fluorescence correlation spectroscopy, raster image correlation spectroscopy, and fluorescence lifetime imaging-Förster resonance energy transfer, we have found that a myosin motor is involved in trafficking of the NaPi cotransporters and also that Npt2a and Npt2c seem to have different affinities for the PDZ protein Na+/H+ exchanger regulatory factor 1. Further application of these techniques will provide additional insights into NaPi trafficking and regulation.